Biologia populacional do camarão-ferrinho Rimapenaeus constrictus (Stimpson, 1874) (Decapoda: Penaeoidea) na região de Cananéia, litoral sul do estado de São Paulo - Garcia, Joyce Rocha [UNESP] (2015)
Rimapenaeus constrictus presents a wide geographical distribution and environmental factors that influence their abundance and distribution pattern are still poorly understood. The aims of the present study were describe the environmental factors acting in Cananeia region and understand more clearly the influence of the environmental conditions on the R. constrictus. The shrimps were collected from monthly samples in Cananéia region, South coast of São Paulo state, from July 2012 through May 2014 using a shrimp boat outfitted with double-rig nets, at isobaths in 5 to 20 feet deep. Environmental factors were obtained in the water column by a Multiparameters probe and the sediment by a Petersen grab. Were collected 1784 individuals mainly distributed in salinities higher than 30 and variable types of sediment, since silt + clay until very coarse sandy, in temperatures ranging between 17 and 29°C and in the lower clorophyll concentrations (up to 14μg/L). The environmental factors that influenced the distribution of the species were salinity and temperature (Multiple Regression, p < 0.05). The abundance did not differ among the seasons, but differed among stations (Tukey, p < 0.05). Cananéia was presented as a dynamic region of complex environmental characteristics. Rimapenaeus constrictus seems to be a very generalist species in the choice of substrate and probably it has physiology eurythermal and stenohaline, and salinity was considered as a limiting factor in its distribution